Mechanism of Qihuang needle therapy in the management of tic disorders: a clinical trial protocol - Tang, Yuyuan; Wu, Jun'e; Xu, Zhirui; Fan, Baochao; Li, Xiangli; Jin, Bingxu; Tang, Chunzhi (Frontiers in Neurology, 2023)
Background: Qihuang needle therapy is a newly developed acupuncture therapy to treat tic disorders in clinical practice. However, the mechanism to relieve tic severity remains unknown. Disturbances in intestinal flora and circulation metabolites are perhaps the potential pathogenesis of tic disorders. Because of this, we present a protocol for a controlled clinical trial using multi-omics analysis to probe the mechanism of Qihuang needle in managing tic disorders. Methods: This is a matched-pairs design, controlled, clinical trial for patients with tic disorders. 36 Participants will be allocated to either an experiment group or a healthy control group. Baihui 37 (GV20), Yintang (EX-HN3), and Jueyinshu (BL14) have been selected as the main acupoints. In the experiment group, Qihuang needle therapy will be administered for a month; the control group will receive no interventions. Expected outcomes: The change in severity of the tic disorder is set as the main outcome. Secondary outcomes include gastrointestinal severity index and recurrence rate, which will be calculated after a 24-week follow-up. Gut microbiota, measured by 16S rRNA gene sequencing; serum metabolomics, assessed via LC/MS; and serum zonulin, assessed by enzyme-linked immunosorbent assay (ELISA), will be used as biological specimen analysis outcomes. The present study will investigate the possible interactions between intestinal flora, serum metabolites, and improvement of clinical profiles, which may shed light on the mechanism of Qihuang needle therapy for tic disorders. Trial registration: This trial is registered at the Chinese Clinical Trial Registry 48 (http://www.chictr.org.cn/). Registration number: ChiCTR2200057723, Date: 2022–04-14